An Excursus into Hearing Loss - Hatzopoulos, Stavros; Ciorba, Andrea (IntechOpen, 2018)
The main objective of this volume is to diffuse the latest information related to hearing loss, which is among the most prevalent chronic disabilities worldwide. Nowadays, it is clear that the identification and rehabilitation of hearing impairment, when possible, have to be adequately and promptly managed because hearing loss can seriously interfere with psychosocial development, family dynamics, and social interactions. This book has been edited with a strong educational perspective (all chapters include an extensive introduction to their corresponding topic and an extensive glossary of terms). This book contains various materials suitable for graduate students in audiology, ENT, hearing science, and neurosciences.